Profitability Moderates The Influence of Good Corporate Governance (GCG) and Corporate Social Responsibility (CSR) Disclosure on The Company's Value - Lailatus Sa'adah; Wardhani , Emeralda Aprilia; Soedarman, Mohamad; Fernanda, Hadiana (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the effect of Good Corporate Governance (GCG) and Corporate Social Responsibility (CSR) disclosure on firm value, with profitability as a moderating variable, in mining companies listed on the Indonesia Stock Exchange during 2022–2024. Using a quantitative approach, data from 16 companies (48 observations) were analyzed using Partial Least Squares (PLS). The results show that GCG and CSR positively and significantly affect firm value. Profitability significantly weakens the relationship between GCG and firm value but does not moderate the relationship between CSR and firm value. These findings highlight the importance of governance and CSR practices in enhancing firm value.